FISH FAUNA IN GUNUNG HALIMUN NATIONAL PARK AND THE ADJACENT AREA - Ike Rachmatika; Djadja S Sjafei; W Nurcahyadi (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Gunung Halimun National Park is known to be the area of head waters of a number river systems originate. However,there has been no information on fishes diversity at this area.In this regard, a series of ichthyofauna study was conducted from 1996 to 2000. Thirty seven species belonging to 13 families and 26 genera have been found in the rivers and streams in Gunung Halimun National Park and its adjacent area.Gobiidae was dominant, comprising 13 species or 36,36 %, followed by Cyprinidae comprising 5 species or 16.13 %.These Gobioid species were derived from Cisukawayana and Cimaja River, two of the rivers existing in Gunung Halimun National Park which flow south, to the Indian Ocean. In river flowing north i.e, Cikaniki, Ciberang and Cidurian, even from the middle of Cisadane River these fishes were not found. The fishes species which were found in common in rivers flowing north and south were Rasbora aprotaenia,Puntius binotatus, Channa gachua, Clarias batrachus, Poecilia reticulata and Xiphoporus helleri. Up to the present ten fish species were found within the park such as R. aprotaernia, P. binotatus, T. tambra, C. gachua, P. reticulata, P. latipinna, Cyprinus carpio, Monopterus albus, Glyptothorax platypogon and Lentipes sp. It was found that genus Lentipes and Schismatogobius marmoratus extend their range to Java (new record for Java) as well as Rasbora aprotaenia extends its range to southern Java.